High conservation value forests for burn‐associated saproxylic beetles: an approach for developing sustainable post‐fire salvage logging in boreal forest. Issue 5 (10th June 2016) - Boucher, Jonathan; Hébert, Christian; Ibarzabal, Jacques; Bauce, Éric
Abstract: Fire‐killed timber is considered as a loss of potential revenues and is thus increasingly salvaged, though not without concerns for biodiversity conservation. Indeed, a large diversity of burn‐associated saproxylic beetles use recently burned trees. This study intends to reduce potential impacts of salvage logging on biodiversity by identifying high conservation value forests (HCVFs) for burn‐associated beetles, which are considered the most at risk. In five burns ignited naturally in 2010 in the eastern Canadian boreal forest, we selected 31 and 29 stands of black spruce and jack pine respectively. Three 50‐cm bole segments were retrieved from each stand and placed in emergence cages to measure tree utilisation by saproxylic beetles. This yielded 7235 beetles from 103 taxa, of which 67 were considered rare (<5% occurrence in logs) and 36 as common taxa (>5% occurrence in logs). Among the common taxa, we identified six groups of ecologically related species using co‐occurrence‐based hierarchical clustering, among which three were mainly formed by opportunistic species that are currently of little concern in a post‐fire logging context. The three other groups were formed by burn‐associated species that could be affected by salvage logging. HCVFs include jack pine stands and large trees of either tree species of low‐ to mid‐range burn severity. We also recommend retaining the periphery of burned stands, as ecotones are rich habitats used by several burn‐associated species that are found in low numbers in green forests but they benefit from burned habitats by increasing their populations significantly.